Essentialities of Ratifying CED in Thailand: Human Rights amid Covid-19 Pandemic - Siwarut Laikram; Shubham Pathak (Emerging Science Journal, 2022)
The Covid-19 pandemic delayed the ratification of several internal laws, reforms, and amendments, especially in developing countries such as Thailand, resulting in limited human rights for the populations. There is a unique violation of human rights inclusive of the right to life, the right not to be tortured, the right to liberty and safety of persons which are very important to international and civil society. This research explores the enforcement measures of the International Convention for the Protection of All Persons from Enforced Disappearance (CED). Thailand is currently in the process of ratifying its membership in CED. This ratification process will contribute towards Thailand for holding an important position to fulfill its obligations as a State Party member of this Convention. Thailand has been drafting internal laws and regulations to be consistent with the CED to recognize and protect lawful human rights. People must not be forced to disappear because such action is a serious criminal offence that must be punished appropriately under the CED. In addition, the injured persons shall be treated fairly and equally in accordance with the objectives and purpose of CED, and the Member of Parliament (MP) shall legislate and support the enactment in accordance with the Convention's obligations. In accordance with international mechanisms, these measures will further enhance the promotion and protection of Thailand's human rights. Therefore, Thailand should complete the ratification process at the earliest to develop more efficient domestic legal measures and mechanisms. Similarly, ratification would be consistent with Article 16 of the Sustainable Development Goals (SDGs), which will contribute to security and enhance a peaceful society by providing access to justice to all people in Thailand. Doi: 10.28991/esj-2022-SPER-05 Full Text: PDF